1999
DOI: 10.1023/a:1006358222037
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The hepatic mitochondrial carnitine palmitoyltransferase (CPT) activity was measured by fluorimetric assay in dairy cows with or without fatty liver. CPT activities in 13 lactating cattle and in 6 non-lactating cows were 304.4+/-86.6 micromol CoA/min per g protein and 169.3+/-84.8 micromol CoA/min per g protein, respectively. This difference was significant (p < 0.05). CPT activities in early lactation (0-110 days after calving), mid-lactation (111-220 days after calving) and late lactation (over 220 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although fatty liver syndrome is one of the most important metabolic diseases in high yielding dairy cows in early lactation [16,23], the pathogenesis of this disease is not thoroughly explored in ruminants; in particular the role of mitochondria has not been established. Pioneering studies assessing fatty acid oxidation in dairy cows showed that carnitine palmitoyltransferase I activity and β-oxidation were impaired in cows with hepatic steatosis [24,25]. Recently, Gao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although fatty liver syndrome is one of the most important metabolic diseases in high yielding dairy cows in early lactation [16,23], the pathogenesis of this disease is not thoroughly explored in ruminants; in particular the role of mitochondria has not been established. Pioneering studies assessing fatty acid oxidation in dairy cows showed that carnitine palmitoyltransferase I activity and β-oxidation were impaired in cows with hepatic steatosis [24,25]. Recently, Gao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously showed that the mRNA abundance of CPT1A and ACO was upregulated in cows with mild fatty liver, indicating a compensatory mechanism (Du et al, 2018b). Others reported cows with fatty liver had significantly lower hepatic CPT activity compared with healthy cows (Mizutani et al, 1999). Thus, the abnormality of fatty acid metabolism, especially the impaired oxidation capability, further facilitates lipid deposition in the liver, leading to the deterioration of fatty liver.…”
Section: Discussionmentioning
confidence: 90%